AL-QUR’AN DAN DIGITALISASI: EDUKASI KARAKTER BERBASIS AL-QUR’AN DALAM KONTEKS DIGITALISASI SEBAGAI UPAYA MENANAMKAN NILAI-NILAI ISLAMI DI MI MUHAMMADIYAH PASIRMUNCANG KABUPATEN BANYUMAS - Sigit Candra NA; Eri Syahriyah; Annisa Lutfiana; M. Misbah (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to analyze the internalization of Qur’anic values in shaping students’ character in the digital era at MI Muhammadiyah Pasirmuncang, Banyumas Regency. Digitalization provides opportunities but also challenges, particularly the decline in spiritual values, discipline, and honesty due to high exposure to digital media. This field research employs a qualitative approach using observation, interviews, and documentation. The findings reveal that Qur’anic values are internalized through Islamic education learning, integration into general subjects, daily Qur’an recitation, congregational prayers, tahfiz programs, and teacher role-modelling. Character strengthening is further supported through extracurricular activities and digital literacy education. The results show increased honesty, responsibility, discipline, and good morality among students. These findings indicate that integrating Qur’anic values is an effective strategy to reinforce students’ character amid rapid digitalization.